Toll-Like Receptors and Cancer: MYD88 Mutation and Inflammation - Wang, James Q.; Jeelall, Yogesh S.; Ferguson, Laura L.; Horikawa, Keisuke (Frontiers in Immunology, 2014)
Pattern recognition receptors (PRRs) expressed on immune cells are crucial for the early detection of invading pathogens, in initiating early innate immune response and in orchestrating the adaptive immune response. PRRs are activated by specific pathogen-associated molecular patterns (PAMPs) that are present in pathogenic microbes or nucleic acids of viruses or bacteria. However, inappropriate activation of these PRRs, such as the Toll-like receptors (TLRs), due to genetic lesions or chronic inflammation has been demonstrated to be a major cause of many haematological malignancies. Gain-of-function mutations in the TLR adaptor protein MYD88 found in 39% of the activated B cell type of diffuse large B cell lymphomas (ABC-DLBCL) and almost 100% of Waldenström’s macroglobulinemia (WM) further highlight the involvement of TLRs in these malignancies. MYD88 mutations result in the chronic activation of TLR signalling pathways, thus the constitutive activation of the transcription factor NFκB to promote cell survival and proliferation. These recent insights into TLR pathway driven malignancies warrant the need for a better understanding of TLRs in cancers and the development of novel anti-cancer therapies targeting TLRs. This review focuses on Toll-like receptors function and signalling in normal or inflammatory conditions, and how mutations can also hijack the TLR signalling pathways to give rise to cancer. Lastly, we discuss how potential therapeutic agents could be used to restore normal responses to TLRs and have long lasting anti-tumour effects.